2017
DOI: 10.5455/ijmsph.2017.02082016622
|View full text |Cite
|
Sign up to set email alerts
|

Whatsapp enhances Medical education: Is it the future?

Abstract: Background: Whatsapp, launched in the year 2009, has exploded to 400 million active users each month. Objectives: The aim of this study was to evaluate the use of Whatsapp to enhance medical education in Indian medical school and also investigate the impact of Whatsapp messenger in their curriculum from the perspective of students. Materials and Methods: The study population included 100 students from the second phase of Sri Muthukumaran Medical College Hospital and Research Institute (SMMCHRI). An experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 5 publications
(5 reference statements)
0
5
0
Order By: Relevance
“…32,80 However, it is unclear whether the differences found in the latter two studies result from the use of SoMe or other confounding variables such as weekly assessment 32 or earlier exposure to educational material. 80 Some studies showed that the rate of utilisation of SoMe positively correlated with test score, 37,39,69 however, others suggested time spent on SoMe had no impact on knowledge improvement. 126 Furthermore, most interventions tested participants' knowledge and skills acquisition in the short term, with limited findings on long-term effectiveness.…”
Section: Academic Performancementioning
confidence: 98%
See 2 more Smart Citations
“…32,80 However, it is unclear whether the differences found in the latter two studies result from the use of SoMe or other confounding variables such as weekly assessment 32 or earlier exposure to educational material. 80 Some studies showed that the rate of utilisation of SoMe positively correlated with test score, 37,39,69 however, others suggested time spent on SoMe had no impact on knowledge improvement. 126 Furthermore, most interventions tested participants' knowledge and skills acquisition in the short term, with limited findings on long-term effectiveness.…”
Section: Academic Performancementioning
confidence: 98%
“…Subjective improvements in students' self-reported performance 56,60,63,123,124 and objective increases in assessment outcomes 33,35,38,40,69,82,125 were reported, including in two studies with controlled designs. 32,80 However, it is unclear whether the differences found in the latter two studies result from the use of SoMe or other confounding variables such as weekly assessment 32 or earlier exposure to educational material. 80 Some studies showed that the rate of utilisation of SoMe positively correlated with test score, 37,39,69 however, others suggested time spent on SoMe had no impact on knowledge improvement.…”
Section: Academic Performancementioning
confidence: 98%
See 1 more Smart Citation
“…WhatsApp is a program that is suitable for use in the educational process. In the field of health education, several programs have integrated WhatsApp into teaching and learning to evaluate its effect (Krishnan et al, 2017 ; Ventola, 2014 ), explore the impact of using WhatsApp on student education (Cetinkaya, 2017 ), determine the effects of sexual education on the level of sexual knowledge and sexual myths in female midwifery students (Gonenc et al, 2021 ), examines the domestication of WhatsApp among young people (Ahad & Lim, 2014 ), find out the lecturer’s perspective on the use of WhatsApp to support the teaching and learning process (Gachago et al, 2015 ), comparing the WhatsApp service to traditional SMS (Church & Oliveira, 2013 ), comparing the effectiveness of teaching via WhatsApp and booklets on the learning rate and emotional status in healthy women related to breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Messaging apps, particularly WhatsApp, are being increasingly used in medical education [ 21 - 23 ]. Alternatively, the use of Telegram, a free, cross-platform, cloud-based messaging app [ 24 ] popular with younger individuals, remains relatively unexplored [ 11 ].…”
Section: Introductionmentioning
confidence: 99%